2014
DOI: 10.1542/peds.2013-2279
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Injuries Among US High School Athletes, 2005/2006–2011/2012

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Shoulder injuries are common among high school athletes. These injuries, both traumatic and overuse, contribute to significant time loss from athletic activity. Understanding sport-specific injury patterns is critical for development of targeted injury prevention programs. WHAT THIS STUDY ADDS:This study is the most comprehensive analysis of high school shoulder injuries to date, providing national injury estimates while examining injury rates, diagnoses, severity, and mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 31 publications
3
68
0
Order By: Relevance
“…Especially ankle and knee injuries are often reported as there are studies only focusing on these injuries [14][15][16]20,21,25,29,30,34,36,44,45]. There are two studies focusing only on shoulder injuries [17,42]. For detailed information on the incidence of injuries see Table 1 and Figure 1, the van Mechelen's 'sequence of prevention' [2].…”
Section: Musculoskeletal Injuries In Basketball: Occurrence and Etiologymentioning
confidence: 99%
“…Especially ankle and knee injuries are often reported as there are studies only focusing on these injuries [14][15][16]20,21,25,29,30,34,36,44,45]. There are two studies focusing only on shoulder injuries [17,42]. For detailed information on the incidence of injuries see Table 1 and Figure 1, the van Mechelen's 'sequence of prevention' [2].…”
Section: Musculoskeletal Injuries In Basketball: Occurrence and Etiologymentioning
confidence: 99%
“…In high school football in the USA, there are approximately 480,000 shoulder injuries per year [1]. In addition to the level of competition, the profile of football-related injuries is unique to the position [2••, 3, 4].…”
Section: Epidemiologymentioning
confidence: 99%
“…Musculoskeletal injuries range from minor sprains and strains to career-ending tears, ruptures, and fractures. In football, possible mechanisms of injury include player-toplayer contact, player-to-surface contact, overuse/repetitive injuries, and noncontact ligament tears and muscle strains (7,15,19,42).…”
Section: Introductionmentioning
confidence: 99%
“…High school football accounts for approximately 480,000 shoulder injuries yearly with 9.0% of these shoulder injuries requiring surgical management (42). Brophy et al (7) found that three of the top 15 musculoskeletal diagnoses made at the National Football League (NFL) combine between 1987 and 2000 were related to shoulder pathology.…”
Section: Introductionmentioning
confidence: 99%